1984
DOI: 10.1063/1.526089
|View full text |Cite
|
Sign up to set email alerts
|

Necessary conditions for a unique solution to two-dimensional phase recovery

Abstract: In this paper we show that although in one dimension multiplicity of solutions to the phase reconstruction problem presents a serious problem, in two or more dimensions multiplicity is pathologically rare. We derive from a given solution pair (g,G) necessary conditions for the existence of alternative solution pairs (h,H), and a characterization of their form. The mathematical tools employed are from the theory of functions of two complex variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
2

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 6 publications
0
66
0
2
Order By: Relevance
“…However, this is often not the case. Mathematically, it has been shown that multiple solutions are rare for two-dimensional (2D) and 3D specimens (11). By using this oversampling method, the phase information has recently been retrieved ab initio from the experimental diffraction pattern of a 2D noncrystalline specimen (a series of dots of 1͞10th micron dimensions) (12).…”
mentioning
confidence: 99%
“…However, this is often not the case. Mathematically, it has been shown that multiple solutions are rare for two-dimensional (2D) and 3D specimens (11). By using this oversampling method, the phase information has recently been retrieved ab initio from the experimental diffraction pattern of a 2D noncrystalline specimen (a series of dots of 1͞10th micron dimensions) (12).…”
mentioning
confidence: 99%
“…The possibility of inverting a set of oversampled Fourier amplitudes (without phases) depends on the dimensionality: There is no unique solution in 1D [18], but it has been argued that one may be found if oversampling is possible in 2D and 3D [19,20]. In the seminal works [12,13], the object recovered was a 2D projection of 2 non-periodic dimensions.…”
Section: A Basic Algorithmmentioning
confidence: 99%
“…In higher dimension an entire function can be irreducible and the above factorisation may be trivial i.e. zero-flipping may be impossible, see [19], [4] for details. Example 1 : Let H be a fixed function with support in −…”
Section: The Phase Retrieval Problemmentioning
confidence: 99%